2013
DOI: 10.1089/thy.2013.0045
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Incidence of Thyroid Cancer: The Influence of Access to Care

Abstract: Markers for higher levels of health care access, both sociodemographic and age-based, are associated with higher papillary thyroid cancer incidence rates. More papillary thyroid cancers are diagnosed among populations with wider access to healthcare. Despite the threefold increase in incidence over three decades, the mortality rate remains unchanged. Together with the large subclinical reservoir of occult papillary thyroid cancers, these data provide supportive evidence for the widespread overdiagnosis of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
315
3
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 448 publications
(347 citation statements)
references
References 44 publications
17
315
3
12
Order By: Relevance
“…Thus, a large pool of subclinical TC exists in the population. The discovery of this subclinical pool of TC lesions is directly associated with the access of individuals to health care, as has been demonstrated in a prior analysis of the SEER database (19). During the period 2000-2012, we have identified four important pathways for the detection of subclinical thyroid cancer, as shown in Figure 1.…”
Section: Limitations and Strengthsmentioning
confidence: 54%
“…Thus, a large pool of subclinical TC exists in the population. The discovery of this subclinical pool of TC lesions is directly associated with the access of individuals to health care, as has been demonstrated in a prior analysis of the SEER database (19). During the period 2000-2012, we have identified four important pathways for the detection of subclinical thyroid cancer, as shown in Figure 1.…”
Section: Limitations and Strengthsmentioning
confidence: 54%
“…A recent ecologic study using the Surveillance, Epidemiology and End Results (SEER) data indicated that higher levels of healthcare access are associated with higher papillary thyroid cancer rates, which provided supportive evidence for the overdiagnosis of thyroid cancer (3). However, other studies offered divergent opinions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of thyroid incidentalomas is certainly one of the causes of the so-called "thyroid cancer epidemic", i.e. the increase in the number of differentiated thyroid cancers (DTC) [3]. The widespread use of ultrasonography (US) and subsequent fine-needle aspiration biopsy undoubtedly coincided with the larger number of small, clinically occult thyroid cancers [3].…”
mentioning
confidence: 99%
“…the increase in the number of differentiated thyroid cancers (DTC) [3]. The widespread use of ultrasonography (US) and subsequent fine-needle aspiration biopsy undoubtedly coincided with the larger number of small, clinically occult thyroid cancers [3]. Another source of thyroid incidentalomas is the increasing rate of reporting of thyroid lesions during other nonthyroid imaging investigations (carotid US imaging, CT, 18 F-FDG PET [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation